A systematic literature review of quantitative research Islamic pilgrimage tourism research era 2000 to 2021 - Mohd Radzi, Ras Afirina; Hussin, Siti Rahayu; Ab Rahman, Suhaimi; Abdullah, Zulhamri (Human Resource Management Academic Research Society, 2021)
Purpose: The aim of this study is to examine and systematically review of the existing literature on Islamic pilgrimage tourism towards crisis. Furthermore, this study seeks to explore the systematic literature to deliver the trends and categorization regarding the recent publication of Islamic pilgrimage. Design/methodology/approach – Preferred Reporting Items for Systematic Review was adopted for current systematic literature review. Search strategy was applied on different databases including Taylor & Francis, Dimensions.ai, Google Scholar, Scopus and the collection of articles were selected from high impact journals published between 2000 to 2021. The search item was classified according to inclusion and exclusion criteria. Findings – In this selected quantitative study, around 49 articles were extracted in total, out of 129 papers were collected. All of the articles selected were from high impact journals. The analyzed data was resulted in map of the research field, which was presented under perspectives: geographical location of authors, types of study, number of citations, prolific journals, extracted themes from various studies, sample size and method of analysis. Moreover, the primary research focuses on Islamic pilgrimage tourism. The majority of the studies were focused on Islamic pilgrimage. Research limitations/implications –The study identifies as ‘stock take’ of Islamic pilgrimage studies as a spiritual journey that could be strategically used by research article. Articles that include in this systematic literature review only include from high ranked journal, which may perceive as a limitation. Other limitation is the study limited to four different databases and articles that are written in English. Practical implications – Future researchers can review the result of the current systematic literature review to set the direction of their study in the area of Islamic pilgrimage tourism. These results can be used by researchers to widen the knowledge about extent of research that conducted in this area. Managerial can develop policies based on Islamic pilgrimage.Originality/value – This review provides a strong contribution to Islamic pilgrimage.